2016
DOI: 10.1103/physrevd.94.044023
|View full text |Cite
|
Sign up to set email alerts
|

Static spherically symmetric Kerr-Schild metrics and implications for the classical double copy

Abstract: We discuss the physical interpretation of stress-energy tensors that source static spherically symmetric Kerr-Schild metrics. We find that the sources of such metrics with no curvature singularities or horizons do not simultaneously satisfy the weak and strong energy conditions. Sensible stress-energy tensors usually satisfy both of them. Under most circumstances, these sources are not perfect fluids and contain shear stresses. We show that for these systems the classical double copy associates the electric ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
110
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 13 publications
4
110
0
Order By: Relevance
“…(78) instead indicate that, because of scalar charge, the double copy of the Coulomb field is neither a vacuum spacetime nor is it equivalent to Kerr-Schild by coordinate transformations. To see this latter assertion, note that the general d-dimensional spherically symmetric Kerr-Schild metric, [11] in Schwarzschild form…”
Section: Color-kinematics Correspondencementioning
confidence: 99%
“…(78) instead indicate that, because of scalar charge, the double copy of the Coulomb field is neither a vacuum spacetime nor is it equivalent to Kerr-Schild by coordinate transformations. To see this latter assertion, note that the general d-dimensional spherically symmetric Kerr-Schild metric, [11] in Schwarzschild form…”
Section: Color-kinematics Correspondencementioning
confidence: 99%
“…This was first raised in [6] which proposed a double copy mapping between nonperturbative classical solutions in pure Yang-Mills theory and Einstein gravity. See [7,8] for related work. In [9], it was found that there is a double copy of perturbative classical radiating solutions in any spacetime dimension d. On the Yang-Mills side, the setup of [9] consists of a set of radiating color charges, interacting self-consistently by gluon exchange.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] within the context of classical Kerr-Schild solutions to the Einstein equations, and further developed in Refs. [11]. More recently, Ref.…”
Section: Introductionmentioning
confidence: 99%